Muscular activity patterns of female and male athletes during the flat bench press - Gołaś, Artur; Maszczyk, Adam; Pietraszewski, Przemysław; Wilk, Michał; Stastny, Petr; Strońska, Katarzyna; Studencki, Marcin; Zając, Adam (Biology of Sport, 2018)
The bench press (BP) is a complex upper body exercise in which substantial external loads can be used, demanding high neuromuscular activity. The aim of this study was to compare electromyographic (EMG) activity between female and male athletes during the flat bench press. Five male and five female athletes participated in this study. The main session included four sets of one repetition of the flat bench press with the load of 55, 70, 85 and 100% of the one-repetition maximum (1RM). The activity of four muscles was analysed: the pectoralis major (PM), the anterior deltoid (AD), the lateral head of the triceps brachii (TBlat) and the long head of the triceps brachii (TBlong). The main finding of the study was that the muscle activity pattern differed between women and men during the bench press depending on the external load. The non-parametric Kruskal- Wallis ANOVA for males showed differences between the TLpeak values recorded for different loads (55%-100% 1RM) during the bench press (chi-square = 15.3, p = 0.009) and AD peak (chi-square = 19.5, p = 0.001). The non-parametric Kruskal-Wallis ANOVA for females showed differences between the AD peak values recorded for different loads (55%-100% 1RM) during the bench press (chi-square = 12.1, p = 0.018).